Self-Efficacy a Critical Factor of Information System: An Investigation using DeLone McLean - Tri Lathif Mardi Suryanto; Djoko Budiyanto Setyohadi; Akhmad Fauzi (IAES Indonesia Section, 2018)
This paper examines what influences Attitude towar usage (ATU) as the expectation of the application of Employee Information System (EIS) with high success rate, this research is observed through cognitive value using approach theory of information system success model DeLone and McLean Model (DMM) and affective value using the Human Resource quality theory (HRQ) and the Self-Efficacy (SE) model. The overall data was obtained by providing questionnaires to employees at the Higher Education and using WarpPLS and SEM as a method of analysis. This study found that, because the EIS was positioned as a compulsory system, our study showed that only Self-Efficacy would affect Attitudes toward the Use of EIS. The quality of human resources, as other Affective factors, has no effect on Attitudes towards usage of EIS.